Phytoclimatic characterization of holm-oak provenances (Quercus ilex L.) in the Central-Northern Iberian Peninsula - Garcia Lopez, J. M.; Gonzalo Jimenez, J.; ALLUÉ CAMACHO, C. (Forest Systems, 2002)
This paper presents some contributions to the phytoclimatic characterization of stands of holm-oak (Quercus ilex. L.) in the centre-north of the Iberian Peninsula and the testing of a method of phytoclimatic homologation applicable to the characterization of provenances of the species. For the phytoclimatic characterization, 432 sampling points in the Province of Burgos were considered, corresponding to the centres of cartographic tessellae of actual vegetation in which holm-oak was the principle species of the forest (18,965 ha). The phytoclimatic diagnosis followed the phytoclimatic models of Allué-Andrade. Phytoclimatic territorial models were constructed in digital format on the basis of preliminary territorial factorial estimations, which were used to determine phytoclimatic terns. Based on the establishment of phytoclimatic ambits for the existence of holm-oak stands in Burgos and stratification in accordance with the five phytoclimatic subtypes (VI(IV)1, VI(IV)2, VI(VII), VI(V) and VI), phytoclimatic homologation was performed in three phases of increasing strictness, all based on a comparison of phytoclimatic terns derived from the general and specific phytoclimatic systems. In the strictest homologation, an adequate and territorially compact degree of discrimination was achieved for 2.622.500 ha (Quercus ilex subsp. ballota) and 116.00 ha (Quercus ilex subsp. ilex) in the centre-north of the Iberian Peninsula. The marked edaphic azonality of the species was an important factor in the interpretation of the results.
Keywords: holm-oak; homologation; phytoclimatology; provenances; Quercus ilex L. subsp. ballota (Desf.) Samp.; Quercus ilex L. subsp. ilex

Phytoclimatic characterization of holm-oak provenances (Quercus ilex L.) in the Central-Northern Iberian Peninsula - Garcia Lopez, J M; Gonzalo Jimenez, J; ALLUÉ CAMACHO, C (Forest Systems, 2002)
This paper presents some contributions to the phytoclimatic characterization of stands of holm-oak (Quercus ilex. L.) in the centre-north of the Iberian Peninsula and the testing of a method of phytoclimatic homologation applicable to the characterization of provenances of the species. For the phytoclimatic characterization, 432 sampling points in the Province of Burgos were considered, corresponding to the centres of cartographic tessellae of actual vegetation in which holm-oak was the principle species of the forest (18,965 ha). The phytoclimatic diagnosis followed the phytoclimatic models of Allué-Andrade. Phytoclimatic territorial models were constructed in digital format on the basis of preliminary territorial factorial estimations, which were used to determine phytoclimatic terns. Based on the establishment of phytoclimatic ambits for the existence of holm-oak stands in Burgos and stratification in accordance with the five phytoclimatic subtypes (VI(IV)1, VI(IV)2, VI(VII), VI(V) and VI), phytoclimatic homologation was performed in three phases of increasing strictness, all based on a comparison of phytoclimatic terns derived from the general and specific phytoclimatic systems. In the strictest homologation, an adequate and territorially compact degree of discrimination was achieved for 2.622.500 ha (Quercus ilex subsp. ballota) and 116.00 ha (Quercus ilex subsp. ilex) in the centre-north of the Iberian Peninsula. The marked edaphic azonality of the species was an important factor in the interpretation of the results.
Keywords: holm-oak; homologation; phytoclimatology; provenances; Quercus ilex L. subsp. ballota (Desf.) Samp.; Quercus ilex L. subsp. ilex